2019
DOI: 10.1093/jxb/erz302
|View full text |Cite
|
Sign up to set email alerts
|

CEPR2 phosphorylates and accelerates the degradation of PYR/PYLs in Arabidopsis

Abstract: CEPR2 interacts with some PYLs to promote their phosphorylation and degradation, whereas ABA inhibits this process. Thus, CEPR2 balances the growth regulation and stress response in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 49 publications
2
100
0
1
Order By: Relevance
“…These results indicated that NRT1.2 enhanced ABA signaling. In contrast, a previous study indicated that CEPR2 inhibited ABA signaling(Yu et al, 2019), suggesting that CEPR2 might negatively regulate NRT1.2.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…These results indicated that NRT1.2 enhanced ABA signaling. In contrast, a previous study indicated that CEPR2 inhibited ABA signaling(Yu et al, 2019), suggesting that CEPR2 might negatively regulate NRT1.2.…”
Section: Resultsmentioning
confidence: 64%
“…To investigate the regulatory mechanisms underlying the response of CEPR2 to ABA, we compared the phosphoproteomes of wild-type (WT) Arabidopsis seedlings to those of CEPR2-OE-9, a previously described Arabidopsis line overexpressing CEPR2 (Yu et al, 2019). We identified 169 differentially expressed phosphopeptides ( p ≤ 0.05 and fold-change ≥ 1.20 or ≤ 0.8), of which 97 (belong to 78 proteins) were upregulated and 72 (belong to 68 proteins) were downregulated (Supplementary Excel 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations